Profissão para homem?: a escolha feminina por cursos de recrutamento majoritariamente masculino na UFMG - Sandra Regina Dantas Flontino (2016)
The dissertation "Job for man? The female choice by mostly male recruitment courses at UFMG" investigates influences of gender assignments in the choice of professions. Historically there has been a significant increase in female participation in higher education, but such participation is a segmented way, with a large variation as the courses and areas. Several studies point to a dichotomy in this context: Human area is more feminine; Exact area, more male, which shows that gender remains an important path of learning paths and career choices. In this sense, it is necessary to understand the students enrolled in courses represented as male to, through the analysis of their school life, understand the unique status of women in socially masculinized professions. Data provided by the Dean of Undergraduate UFMG were used to identify the university courses with less presence and female students examine the public profile at the university as a whole and in courses chosen for this job: Mechanical Engineering and Physics. In addition, it was decided to enrich the data with the construction of a separate questionnaire, applied to all / as the / the students, the first in class and second periods of the two courses. With these more general data, broke to the interview stage, which only took place with the women of the two courses studied, in order to reap closer to research objectives elements. Based on the organization and analysis of all these elements, we seek to understand the students preparing to be physical and mechanical engineers and how they perceive their careers and their professional choices. The research has shown, among other features, the process of choosing a college is hard and bumpy path often trodden in an intricate process of self-selection that Bourdieu (1998) called "the choice possible". However, the perception of the students interviewed have a hopeful tone that the achievements already made on gender concepts can lead to a more egalitarian scenario in society in the near future.